Rethinking renewable energy sustainability: The hidden carbon footprint of critical metals - Tarkun, Savas; Tok, Serife Akinci (Pergamon-Elsevier Science Ltd, 2025)
As the global energy transition accelerates, the environmental sustainability of renewable energy technologies faces growing scrutiny. This study employs the external connectedness decomposition methodology of Gabauer and Gupta (2018) to analyze the pairwise dynamics between global CO2 concentrations and the prices of critical metals-aluminum, copper, nickel, and zinc-integral to renewable energy systems. Using a TVP-VAR model, we uncover that while renewable technologies promise reduced carbon emissions, the energy-intensive production of these metals significantly contributes to CO2 emissions, creating a paradox at the heart of sustainability. The findings reveal CO2 as a highly reactive and influential variable within the system, amplifying the complex interdependencies between energy transitions and material production. This research underscores the urgent need for innovative policies and technologies that decouple metal production from carbon emissions, ensuring that renewable energy transitions align with global climate goals.
Keywords: Renewable energy; Carbon emissions; Metal prices; External connectedness; Sustainable production